Dynamic Governance Dalam Pengelolaan Pedagang Kaki Lima Di Alun-Alun Kota Malang - Anif Diyan Firmansyah; Hayat Hayat; Septina Dwi Rahmawati (Journal of Innovative and Creativity, 2025)
This study analyzes the implementation of the Dynamic Governance concept in managing street vendors at Malang City Square by Diskopindag. A descriptive qualitative approach was applied through interviews, observations, and documentation. The findings show three key dimensions: Thinking Ahead, reflected in plans to relocate vendors to Pasar Baru Barat; Thinking Again, in the shift from repressive control to empowerment; and Thinking Across, in cross-sector collaboration with Satpol PP, the Transportation and Environmental Departments. However, implementation remains limited by weak coordination, lack of accurate data, low digital literacy, and minimal public participation. Strengthening data systems, inter-agency collaboration, and vendor engagement is crucial to realizing adaptive and sustainable governance of street vendors in Malang.